2011
DOI: 10.1093/hmg/ddr326
|View full text |Cite
|
Sign up to set email alerts
|

The Sirtuin 2 microtubule deacetylase is an abundant neuronal protein that accumulates in the aging CNS

Abstract: Sirtuin 2 (SIRT2) is one of seven known mammalian protein deacetylases homologous to the yeast master lifespan regulator Sir2. In recent years, the sirtuin protein deacetylases have emerged as candidate therapeutic targets for many human diseases, including metabolic and age-dependent neurological disorders. In non-neuronal cells, SIRT2 has been shown to function as a tubulin deacetylase and a key regulator of cell division and differentiation. However, the distribution and function of the SIRT2 microtubule (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
158
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(182 citation statements)
references
References 47 publications
13
158
2
5
Order By: Relevance
“…In paper I, analysis of cDNA from several human cell lines revealed the existence of a new splice variant and confirmed the previously reported data from mice [143,144].…”
Section: The Nuclear Isoform Of Sirt2 Does Not Deacetylate Nuclear Tasupporting
confidence: 86%
“…In paper I, analysis of cDNA from several human cell lines revealed the existence of a new splice variant and confirmed the previously reported data from mice [143,144].…”
Section: The Nuclear Isoform Of Sirt2 Does Not Deacetylate Nuclear Tasupporting
confidence: 86%
“…SIRT2 mainly exists in 2 different isoforms [Isoform 1 (389 aa: 43 kDa) and isoform 2 (352 aa: 39 kDa)] and both these isoforms showed increased expression during senescence. 28 It has to be noted that SIRT2 antibody identified both the isoforms on the immunoblot with almost similar intensity. For quantification, the fold increase for both the isoforms were calculated and their average was taken as the total increase in SIRT2 pool which was approximately 3 fold higher in senescent cells compared to the control (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…In mouse brain 3 different isoforms of SIRT2 have been detected, SIRT2.1, 2.2. and 2.3, of which the 2.3 isoform showed an increase with age in the central nervous system. 28 However, a recent report indicated that increase in SIRT2 levels in aged rat brain is specific only to occipital region and no other regions. 36 In contrast to the results of our study, a recent report by Kilic Eren et al, (2015) 37 showed decrease in SIRT2 levels in resveratrol induced premature senescence in human fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, few studies have focused on the microtubule cytoskeleton of aging cells, except for the acetylation‐induced instability of neuronal microtubules in the context of dementia (Maxwell et al., 2011; Raes & Remacle, 1987; Schatten, Chakrabarti & Hedrick, 1999). Our microscopic evaluation did not reveal gross changes in the organization of tubulin and acetylated tubulin that could explain the observed changes in autophagic vesicular trafficking.…”
Section: Discussionmentioning
confidence: 99%